Studi Kontekstualisasi tentang Perjumpaan Aluk Sola Pemali dengan Kitab Suci Kristen dalam Merajut Keharmonisan bagi Masyarakat Sillanan - Tumanan, Yohanis Luni; Timu, Jovier (Institut Agama Kristen Negeri Toraja, 2023)
The aims of this study is to gain an in-depth comprehension of the teachings of Aluk Sola Pemali among Aluk Todolo adherents, and to facilitate a theological dialogue based on scriptural interpretation aimed at fostering harmony. This study employs a method that is qualitative and descriptive in nature, which involves both an analysis of relevant literature and conducting field research. To create harmony within the Sillanan society, field research was conducted by means of in-depth interviews to ascertain the meaning of Aluk sola Pemali, which was then compared with the teachings of the Scriptures. The research findings indicate that the encounter between Aluk sola Pemali and the Scriptures shares a common core teaching. In Aluk sola Pemali, the emphasis is on the way of life by Tintiri Buntu as a guiding principle, while in the Scriptures, rules and regulations are contained within the Law of Moses and the Law of Christ, serving as a way of life with a similar core teaching to Aluk sola Pemali. The particularistic differences between the two represent a beauty that needs to be embraced with an attitude of tolerance in weaving harmony.